Soft Power through Pilgrimage: Analyzing Saudi Arabia’s 2024 King Salman Omra Program in Indonesia - Jayanti, Amalia (Jurnal Transformasi Global, 2024)
This study analyzes Saudi Arabia’s soft power strategy in Indonesia through King Salman’s 2024 Umrah Program. The research focuses on the growing importance of religious diplomacy in strengthening bilateral relations, particularly between Saudi Arabia and Indonesia, the largest Muslim-majority country. It examines how the program operates as a tool of soft power and its impact on bilateral ties.  Using qualitative methods, this research relies on secondary data from government publications, media reports, and scholarly articles. Data collection involves document analysis, and thematic content analysis is employed to interpret the findings. The study reveals that the 2024 King Salman’s guest omra program effectively enhances Saudi Arabia’s religious diplomacy by fostering cultural and religious connections with Indonesia. The program reinforces Saudi Arabia’s leadership within the global Muslim community while promoting bilateral collaboration in areas like education and trade. However, challenges arise for Indonesia in balancing foreign influence with domestic priorities. The findings conclude this program is a strategic soft power tool that strengthens Saudi Arabia’s influence and improves bilateral relations with Indonesia. This research contributes to international relations by illustrating how religious diplomacy can serve as a non-coercive foreign policy instrument to build trust and cooperation between Muslim-majority nations.